ANALISIS PENGARUH NILAI TUKAR (KURS) DOLAR AMERIKA (US$) BI RATE, DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG)DI BURSA EFEK INDONESIA (BEI) - B01108034, Yuliana (Jurnal Pembangunan dan Pemerataan, 2014)
One way to measure the performance of capital market is a stock index. Composite Stock Price Index (IHSG) is the most widely used index and used as a reference on the development activities in the capital market. There are many factors can affect the stock index in the capital market. This research aims to analyze the influence of the BI rate, exchange rate, inflation This research used ARCH/GARCH with 6 variations of (p) and (q). Model feasibility, significance of variable, coefficient sign, AIC dan SIC value are the criterion to choose the best model. This research uses monthly data from the years 2006 – 2012 for each variable. BI rate, exchange rate, inflation as the independent variable, while the dependent variable is IHSG. While the variable of exchange rate was negatively affect to IHSG. In addition, BI rate and inflation have no significant effect on IHSG. Keywords : Composite Stock Price Index (IHSG), macroeconomics variables, integration of world capital markets